UPAYA MENINGKATKAN HASIL BELAJAR KIMIA MELALUI MODEL PENDEKATAN IBL (INQUIRI BASED LEARNING) PADA SISWA KELAS XI BUSANA SMK NEGERI 3 PEKANBARU - Purnamawati, Purnamawati (Perspektif, 2018)
This research is entitled "Efforts to Improve Chemistry Learning Outcomes through an Inquiry Based-Learning IBL Model for Class XI Students in SMK Negeri 3 Pekanbaru". This research is to help students actively find ways to solve quickly and precisely because students experience difficulties in completing chemistry lessons. The purpose of this research is to increase students' motivation in chemistry learning with the Inquiry Based Learning approach. Researchers tried to use the Inquiry Based-Learning approach, through a cycle model class action research that included planning, action, observation, and reflection. The research subjects were students of class XI Clothing at SMK Negeri 3 Pekanbaru as many as 30 students. There are 2 cycles of student motivation learning process, namely: Colloidal Cycle I, Colloidal Cycle II system. Each cycle consists of several stages of meeting. The results obtained from this study show that students' activities in the learning process can be better seen from the comparison of results in the initial observation, only 40% of students who understand and the results are good, in the first cycle increased to 67%, and the second cycle increased to 97%. Attention of students during learning increases. From the above explanation it can be concluded that by using the IBL (Inquiry Based Learning) approach can increase the understanding of chemistry in colloids.